Enhancing Acidic Dye Adsorption by Updated Version of UiO-66 - Naser Al Amery; Hussein Rasool Abid; Shaobin Wang; Shaomin Liu (AMTS and Faculty of Engineering - Universitas Riau, 2020)
In this study, two improved versions of UiO-66 were successfully synthesised. Modified UiO-66 and UiO-66-Ce were characterised to confirm the integrity of the structure, the stability of functional groups on the surface and the thermal stability. Activated samples were used for removal harmful anionic dye (methyl orange) (MO) from wastewater. Batch adsorption process was relied to investigate the competition between those MOFs for removing MO from aqueous solution. Based on the results, at a higher initial concentration, the maximum MO uptake was achieved by UiO-66-Ce which was better than modified-UiO-66. They adsorbed 71.5 and 62.5 mg g-1 respectively. Langmuir and Freundlich isotherms were employed to simulate the experimental data. In addition, Pseudo first order and Pseudo second order equations were used to describe the dynamic behaviour of MO through the adsorption process. The high adsorption capacities on these adsorbents can make them promised adsorbents in industrial areas.